The perspective of all-silicon photonics and systems - Y. Yuan; Y. Peng; S. Cheung; X. Xiao; W. V. Sorin; Z. Huang; D. Liang; A. Kumar; R. Liu; Y. Hu; S. Hooten; S. Palermo; et al. (APL Photonics, 2025)
Silicon photonics has emerged as a transformative solution to address the energy and bandwidth challenges of modern computing and communication systems. While integrating diverse materials with silicon has enhanced the functionality of photonic integrated circuits, these hybrid approaches often face challenges related to scalability, cost, and compatibility with CMOS processes. We provide a comprehensive perspective on advancing high-performance all-silicon photonic devices and systems. By fully leveraging the inherent potential of silicon, diverse functionalities have been demonstrated, including Raman lasers, modulators, photodiodes, and optical memories. This approach outlines a pathway toward fully integrated electronic–photonic circuits on the silicon platform, seamlessly aligned with the existing CMOS infrastructure.